Cu2ZnSnS4 photovoltaic cell with improved efficiency fabricated by high‐temperature annealing after CdS buffer‐layer deposition. (16th October 2016) - Tajima, Shin; Umehara, Mitsutaro; Hasegawa, Masaki; Mise, Takahiro; Itoh, Tadayoshi
Abstract: To improve the photovoltaic properties of Cu2 ZnSnS4 (CZTS) cells, we investigated the effect of both the thickness of the deposited CdS layers and the post‐annealing temperature following CdS deposition on the photovoltaic properties of CZTS cells using a two‐layer CZTS structure. By depositing a thin CdS layer (40 nm) followed by high temperature annealing (603 K), we observed a remarkable increase in the short‐circuit current density because of the enhancement of the external quantum efficiency in the wavelength range of 400–800 nm. The best CZTS cell exhibited a conversion efficiency of 9.4% in the active area (9.1% in the designated area). In addition, we also fabricated a CZTS cell with open‐circuit voltage of 0.80 V by appropriately tuning the composition of the CZTS layers. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Using two‐layer CZTS, we investigated the effects of the thickness of the CdS layers deposited and the post annealing temperature after CdS deposition on the photovoltaic properties of CZTS cells. As a result, the J sc value remarkably increased because of an enhancement of external quantum efficiency in the wavelength range 400–800 nm. The best CZTS cell showed a conversion efficiency of 9.4%. In addition, we have also fabricated the CZTS cell with V OC  = 0.801 V.